2019
DOI: 10.1186/s40337-019-0244-4
|View full text |Cite
|
Sign up to set email alerts
|

Dating app use and unhealthy weight control behaviors among a sample of U.S. adults: a cross-sectional study

Abstract: Background Online dating has become increasingly popular over the years. Few research studies have examined the association between dating apps and disordered eating. In this study, we evaluated the association between dating app use and unhealthy weight control behaviors (UWCBs) among a sample of U.S. adults. Methods Our sample includes 1769 adults who completed an online survey assessing dating app use and UWCBs in the past year. Survey assessed participants’ self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…The following block refers to the risks of dating app use regarding diet and body image. These applications, focusing on appearance and physical attractiveness, can promote excessive concerns about body image, as well as various negative consequences associated with it (e.g., unhealthy weight management behaviors, low satisfaction and high shame about the body, more comparisons with appearance [ 22 , 36 , 67 , 73 ]). These risks have been more closely associated with men than with women [ 61 ], perhaps because of the standards of physical attractiveness prevalent among men of sexual minorities, which have been the most studied collective.…”
Section: Resultsmentioning
confidence: 99%
“…The following block refers to the risks of dating app use regarding diet and body image. These applications, focusing on appearance and physical attractiveness, can promote excessive concerns about body image, as well as various negative consequences associated with it (e.g., unhealthy weight management behaviors, low satisfaction and high shame about the body, more comparisons with appearance [ 22 , 36 , 67 , 73 ]). These risks have been more closely associated with men than with women [ 61 ], perhaps because of the standards of physical attractiveness prevalent among men of sexual minorities, which have been the most studied collective.…”
Section: Resultsmentioning
confidence: 99%
“…Correlations were 0.18 or lower for self-esteem and the scores for app usage, dating behaviour and tinder intensity [13]. A study by Tran et al of almost 1800 adults found that dating application users were significantly more likely to engage in unhealthy weight control behaviours (such as laxative use, self-induced vomiting and use of anabolic steroids) compared to non-users [14].…”
Section: Introductionmentioning
confidence: 99%
“…Future research should build upon our findings by using a larger, more diverse sample to better assess whether UWCBs and binge eating vary across journalists who identify as racial/ethnic minorities (Austin et al, 2011;Story, French, Resnick, & Blum, 1995;Tran et al, 2019). Future work will also need to include a more expansive survey with added questions about body image concerns and the underlying motivations for weight control.…”
Section: Discussionmentioning
confidence: 94%